Correlation of zooclast reflectance with Rock-Eval Tmax values within Upper Ordovician Cape Phillips Formation, a potential petroleum source rock from the Canadian Arctic Islands. (1st September 2018) - Synnott, Dane P.; Dewing, Keith; Ardakani, Omid H.; Obermajer, Mark
Highlights: Correlation between graptolite and chitinozoan reflectance in the range of 0.6–1.0%. Correlation between graptolite and chitinozoan reflectance to Rock-Eval Tmax. A general solution to the conversion of zooclasts to Tmax is proposed. Some soluble hydrocarbon pyrolyses in the temperature range overlaping the S2 peak. Abstract: The lower part of the Cape Phillips Formation (Upper Ordovician, Canadian Arctic) is an ideal unit to test the correlation of graptolite and chitinozoan reflectance, and to compare zooclast reflectance with Rock-Eval pyrolysis Tmax . The Cape Phillips Formation is an organic-rich limestone and shale containing abundant zooclasts, bitumen, and amorphous organic matter, and has biomarker characteristics consistent with a carbonate depositional environment and organic matter derived from marine algae. Random graptolite reflectance on thirty-seven samples in the Rograp range of 0.58%–1.02% (Tmax range of 424–441 °C) were examined. The correlation between random reflectance of graptolite and chitinozoan reflectance was determined to have the following linear model: ( Ro grap ) = 0.11 + 0.814 × ( Ro chi ) whereas the linear correlation between Rock-Eval Tmax (converted to vitrinite reflectance equivalent VRoeqv ) and Rograp and Rochi were determined to be: VRo eqv ( Tmax ) = 0.232 + 0.499 × ( Ro grap ) for random reflectance of graptolites. VRo eqv ( Tmax ) = 0.231 + 0.482 × ( Ro chi ) for chitinozoan. Graptolite and chitinozoan reflectance are generally greater than vitrinite reflectance equivalent, but the difference between the equations to convert graptolite and chitinozoan reflectance to VRoeqv(Tmax ) are so small that the equations could be used interchangeably and may represent a general solution to the conversion of zooclasts reflectance to VRoeqv(Tmax ) in Lower Paleozoic rocks. The correlation between zooclast reflectance and Rock-Eval Tmax improves in samples that have undergone solvent extraction, indicating that hydrocarbons affect Tmax . Sample that has asymmetrical S2 peak on Rock-Eval pyrolysis also has very high total extract yield with resins and asphaltenes as the dominant extracted fractions. Rock-Eval analysis of samples before and after solvent extraction demonstrates that some portion of the soluble hydrocarbon is pyrolysed in the temperature range that overlaps the S2 peak. In extracted samples S2 peaks become more symmetrical and the Tmax value shifts compared to the unextracted samples.